Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Minyak Goreng (Studi Kasus pada Masyarakat Desa Sipispis Kabupaten Serdang Bedagai) - Sariani Purba; Dedi Wahyudi (CIVITAS: Jurnal Studi Manajemen, 2022)
The Purpose of this research is to know how much influence price and product quality and purchasing decision on Minyak Goreng Bimoli at peoples of Desa sipispis. The sample are 108 peoples from Dusun II Desa sipispis,used saturation sampling is provide for every peoples of the population to be sample (population research). Data analysis using partial test ( t test ),  simultaneous test ( f test), and determination coefficient test (R2 ). Data processing used SPSS version 22. Results showed that partial price has effect to purchasing decesion and product quality has no effect to purchasing decesion. Simultaneous price and quality product have positive and significant impact to purchasing decesions, determination coefficient of 13,3% price and product quality have influence on purchasing decesions. While the the remaining is influenced by other factors, such as promotions, and degree of trust peoples.